ANALYSIS OF THE EFFEVTIVENESS OF THE SUB DISTRICT DEVELOPMENT PARTICIPATION PROGRAM AT THE CIBADAK SUB DISTRICT, SUKABUMI DISTRICT - HASANUDIN; IKE RACHMAWATI; SAKTI ALAMSYAH (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2021)
The Subdistrict Development Participation Program (P3K) of Sukabumi Regency is a regional program that is prepared to synergize many and diverse programs, both sector-based and regionally sourced from the Center, Province, or regions that are implemented in the region (Sub-district and or village). In Cibadak District, the first aid program is considered very appropriate because it is expected to be a solution to the problem of lack of community participation in development. However, the implementation of the first aid program in Cibadak District has not been fully effective. This is because the government and the community as program implementers still find obstacles in the lack of quality of the resources they have, thus causing the results of development to be less in line with what was planned. In addition, the first aid program has not been fully implemented properly in targeting its policy objectives. So that in its implementation, it is necessary to refocus the targets that are the priority in the development plan contained in the technical instructions for the first aid program. Then in terms of increasing the HDI, although there has been an increase in the HDI rate and a reduction in the poverty rate, the HDI growth is very small. In fact, as the allocated budget grows, it should leverage higher performance.